Crystal Phase and Surface Morphology of Zeolite-Y Templated Carbon with K2CO3 and ZnCl2 Activation - Ufafa Anggarini; Eva Agustina; Nurul Widiastuti (Universitas Gadjah Mada, 2015)
Zeolite-Y templated carbon (ZTC) has been activated with K2CO3 and ZnCl2. This research aims to compare the characteristics of ZTC with K2CO3 and ZnCl2 activation. ZTC was synthesized via impregnation method followed by carbonization. In this research, activation process was conducted at variation of activator/carbon weight ratio of 1 and 1.50. The activation was carried out by heating up impregnated carbon at 800 °C for 1 h followed by washing to remove inorganic salt. XRD and SEM results indicate that the use of different activator produce ZTC with varied structure and morphology. Diffractogram results showed that the graphitic peak decreased due to K2CO3 activation, whereas graphitic peak increased owing to ZnCl2 activation. Decreasing the graphitic peak indicates that ZTCs have higher pore structure formation. In addition, surface formation of ZTC activated by K2CO3 was higher than by ZnCl2 activation. The higher pore structure formation means the amount of carbon deposited on external surface material was decreased.